Risk management of micro- and macrovascular complications of diabetes mellitus: the importance of glycemic self-control - Olga A. Polyakova; Dinara G. Gusenbekova; Olga D. Ostroumova (LLC "MEDIAFORMAT", 2021)
As the incidence of obesity, unhealthy lifestyles and an aging population increases, the global prevalence of diabetes mellitus (DM) is projected to rise sharply in the coming decades. A significant part of the burden of DM is associated with the development of micro- and macrovascular complications, which are the cause of a deterioration in the quality of life, disability and premature death of patients with DM. Cardiovascular disease (CVD) is the leading cause of death in patients with DM, especially those with type 2 DM The risk of CVD in people with DM is 2-4 times higher than in people without DM, and this risk increases with the deterioration of glycemic control. Disorders of the glycemic profile such as hyperglycemia, hypoglycemia and high variability of glycemia negatively affect the prognosis of patients with DM. Self-monitoring of blood glucose is an effective tool for managing DM, which allows not only achieving the target level of glycated hemoglobin and minimizing glycemic variability, but predicting the risk of severe hypoglycemia.